2000
DOI: 10.1139/f99-268
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic costs of heavy metal exposure in yellow perch (Perca flavescens): in situ estimates with a radiotracer (137Cs) technique

Abstract: While the flow of energy is understood to determine the growth of organisms and the productivity of ecosystems, little is known about the sublethal effect of pollutants on the energetic efficiency of wild populations. We used field estimates of fish growth coupled to in situ estimates of food consumption rates obtained from the mass balance of a globally dispersed, trophically transferred radiotracer ( 137 Cs) to demonstrate the bioenergetic impairment of yellow perch (Perca flavescens) from lakes polluted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 40 publications
3
53
3
2
Order By: Relevance
“…Numerous field studies reported that the condition factor is lower in fish exposed to mixtures of metals, through alterations of enzymatic capacity (Lévesque et al, 2003;Couture and Kumar, 2003) and in some situations, alterations of the food basis in contaminated lakes (Sherwood et al, 2000;Iles and Rasmussen, 2005). Exposure to Cu alone decreased the condition factor and hepatosomatic index in this study, however whether these effects were caused by reduced food consumption or a less efficient capacity to transform food into biomass was not determined.…”
Section: Discussioncontrasting
confidence: 65%
“…Numerous field studies reported that the condition factor is lower in fish exposed to mixtures of metals, through alterations of enzymatic capacity (Lévesque et al, 2003;Couture and Kumar, 2003) and in some situations, alterations of the food basis in contaminated lakes (Sherwood et al, 2000;Iles and Rasmussen, 2005). Exposure to Cu alone decreased the condition factor and hepatosomatic index in this study, however whether these effects were caused by reduced food consumption or a less efficient capacity to transform food into biomass was not determined.…”
Section: Discussioncontrasting
confidence: 65%
“…Fish allocate energetic resources to detoxify metals taken up through food or water, and the presence of relatively high environmental metal concentrations may reduce food availability if concentrations are high enough to induce toxicity in food organisms (Sherwood et al 2000). However, published studies investigating morphometric condition in wild yellow perch populations have led to contradictory conclusions in the literature.…”
Section: Morphometric Fish Conditionmentioning
confidence: 99%
“…These lakes are rapidly recovering and today, brown bullhead (Ameiurus nebulosus), pumpkinseed (Lepomis gibbosus), and various minnows can be captured in Hannah Lake, while Whitson Lake also shelters a growing population of northern pike (Esox lucius) and walleye (Sander vitreus; unpublished data). Yellow perch is also a dominant species in metal-contaminated lakes of Rouyn-Noranda (Sherwood et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lakes surrounding the industrial region of Rouyn-Noranda in northwestern Québec have been affected by mining and smelting operations since about 1927 (Couillard et al 1993). Although the extent of industrial contamination is considerably smaller in the Rouyn-Noranda region than in Sudbury, recent studies have demonstrated elevated concentrations of Cd, Cu, and Zn in contaminated lakes relative to background concentrations (Couillard et al 1993;Brodeur et al 1997;Laflamme et al 2000;Sherwood et al 2000;Levesque et al 2002).…”
Section: Introductionmentioning
confidence: 99%